Rural development policies and programmes in support of rural women: the Italian experience - Navarra V. (Women status in the Mediterranean: their rights and sustainable development, 2009)
In recent times the role played by women in rural development has been given an ever increasing attention, culminating in the insertion of specific measures in Agenda 2000. The EU programs for rural development aim at singling out the factors handicapping the full participation of women in the public and economic life at local level and at developing specific initiatives for this category. The Italian State, in agreement with the EU Commission and by means of Structural Funds, in particular the European Social Fund (ESF), plays an important role in reducing inequality among men and women in matters of employment, thus enforcing the so-called mainstreaming.
International Meeting on Women Status in the Mediterranean: their Rights and Sustainable Development, 2008/06/16-17, Bari (Italy)